2017
DOI: 10.4236/gep.2017.59017
|View full text |Cite
|
Sign up to set email alerts
|

Land Suitability Evaluation for Agricultural Cropland in Mongolia Using the Spatial MCDM Method and AHP Based GIS

Abstract: The purpose of this study was to prepare a cropland suitability map of Mongolia based on comprehensive landscape principles, including topography, soil properties, vegetation, climate and socio-economic factors. The primary goal was to create a more accurate map to estimate vegetation criteria (above ground biomass AGB), soil organic matter, soil texture, and the hydrothermal coefficient using Landsat 8 satellite imagery. The analysis used Landsat 8 imagery from the 2016 summer season with a resolution of 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Therefore, there is a relatively strong interaction between soil type and vegetation distribution. Related studies have also shown that when precipitation is the dominant factor, soil type has an important impact on vegetation growth and rainwater reuse [6,56].…”
Section: Driving Force Of Vegetation Distribution and Changesmentioning
confidence: 99%
“…Therefore, there is a relatively strong interaction between soil type and vegetation distribution. Related studies have also shown that when precipitation is the dominant factor, soil type has an important impact on vegetation growth and rainwater reuse [6,56].…”
Section: Driving Force Of Vegetation Distribution and Changesmentioning
confidence: 99%
“…Erdenee et al [5] have used Landsat TM and ETM data in the detection of changes cropland over Tsagaannuur, Selenge provinces from 1989 and 2000. Otgonbayar et al [41] investigated to prepare a cropland suitability map of Mongolia using Landsat and MODIS (MOD13, MOD15, and MOD17). Furthermore, Enkhjargal et al [42] used MODIS and SPOT time-series remotely sensed data from 2000-2013 to estimate long-term soil moisture content in agricultural regions of Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the yield per hectare of two farms in the same geographical area appears to be different. The evaluation criteria of Munkhdulam (2017) were followed since it was difficult to develop criteria for this sub-topic [20].…”
Section: Pmasmentioning
confidence: 99%